2021
DOI: 10.1098/rspb.2021.1195
|View full text |Cite
|
Sign up to set email alerts
|

Disease-driven mass mortality event leads to widespread extirpation and variable recovery potential of a marine predator across the eastern Pacific

Abstract: The prevalence of disease-driven mass mortality events is increasing, but our understanding of spatial variation in their magnitude, timing and triggers are often poorly resolved. Here, we use a novel range-wide dataset comprised 48 810 surveys to quantify how sea star wasting disease affected Pycnopodia helianthoides , the sunflower sea star, across its range from Baja California, Mexico to the Aleutian Islands, USA. We found that the outbreak occurred more rapidly, killed a greater pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 35 publications
0
43
0
Order By: Relevance
“…Filbee-Dexter and Scheibling [7] have suggested that the barrens state may be unstable because of predation, and that is supported by the positive impact of recovering P. helianthoides populations in our model. Unfortunately, evidence for actual widespread sea star recovery from SSWD is currently equivocal at best [46]. Nevertheless, our model results, which predict a delayed onset of transitions if Steller’s sea cow is present, also predict that recovery times would have been shorter in the presence of the sea cow.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…Filbee-Dexter and Scheibling [7] have suggested that the barrens state may be unstable because of predation, and that is supported by the positive impact of recovering P. helianthoides populations in our model. Unfortunately, evidence for actual widespread sea star recovery from SSWD is currently equivocal at best [46]. Nevertheless, our model results, which predict a delayed onset of transitions if Steller’s sea cow is present, also predict that recovery times would have been shorter in the presence of the sea cow.…”
Section: Discussionmentioning
confidence: 58%
“…The MHW, or blob perturbation, consisted of an abrupt increase of temperature 3.0 ° C in excess of the seasonal cycle, and lasted for 2 years (730 days), after which temperatures returned to the seasonal cycle. The onset of SSWD was also initiated 10 years after burn-in, and was implemented as an exponential decline of the P. helianthoides population, modeled from empirical data of population decline from central and northern California [19]. after which the sea star population was allowed to recover.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations